PREDICTIVE MODEL OF STUDENTS’ INTELLIGENCE QUOTIENT (IQ) BASED ON COGNITIVE ABILITIES IN MATHEMATICS, INDONESIAN LANGUAGE, AND ENGLISH - Sugiyanto Sugiyanto; Setyawati Setyawati; Inta Prihandini; Dewani Roro Rengganis (Universitas Labuhanbatu, 2026)
Purpose – This study aims to analyze the influence of cognitive abilities in Mathematics, Indonesian Language, and English subjects on students’ Intelligence Quotient (IQ).Methodology – This study employed a quantitative approach using multiple linear regression analysis. The research data consisted of academic scores for 82 students across three subjects and their IQ scores. Prior to conducting the regression analysis, descriptive statistics and classical assumption tests were performed, including tests for normality, multicollinearity, and heteroscedasticity.Findings – The regression analysis results from the initial model indicated that Mathematics and Indonesian Language abilities had a positive and significant effect on students’ IQ. In contrast, English ability did not show a significant effect. Therefore, the regression model was simplified by including only the Mathematics and Indonesian Language variables. The final model analysis demonstrated that both variables continued to have a positive and significant effect on students’ IQ. The coefficient of determination indicated that the research model explained approximately 23.3% of the variation in students’ IQ.Contribution – The findings of this study indicate that numerical and verbal abilities help explain students’ cognitive abilities.